Rebel or misunderstood? (Journal of Parents and Teachers, 2023)
The article is a short autobiography where the author tells us some information about her hard childhood. It’s clear that the author feels like a fish out of water that doesn’t fit in the world, but something happened and everything changed.
Keywords: autobiography; education